Chloroplast genomes in seven Lagerstroemia species provide new insights into molecular evolution of photosynthesis genes - He, Ling; Xu, Sujuan; Cheng, Xinnian; Huang, Hanlin; Dai, Hongyu; Wang, Xin; Ding, Zhiyang; Xu, Ming; Gu, Haoran; Yan, Na; Wang, Chunyan (Frontiers in Genetics, 2024)
Lagerstroemia indica is an important commercial tree known for the ornamental value. In this study, the complete chloroplast genome sequence of Lagerstroemia indica 'Pink Velour' (Lagerstroemia 'Pink Velour') was 152,174 bp in length with a GC content of 39.50%. It contained 85 protein coding genes (PCGs), 37 tRNAs, and 8 rRNA genes. 207 simple sequence repeats (SSRs) and 31 codons with relative synonymous codon (RSCU)value>1 were detected. Phylogenetic analysis divided 10 Lagerstroemia species into evolutionary branches of clade A and clade B. We conducted a comparative analysis of Lagerstroemia 'Pink Velour''s complete chloroplast genome with the genomes of 6 closely related Lagerstroemia species from different origins. The structural features of all 7 species were similar, except for the deletion of ycf1 nucleobases at the JSA boundary. The large single-copy (LSC) and the small single-copy (SSC) had a higher sequence divergence than the IR region, and 8 genes that were highly divergent petN, psbF, psbJ, ndhE, ndhD, ndhI, ycf1) had been identified and could be used as molecular markers in future studies. High nucleotide diversity was present in genes belonging to the photosynthesis category. Mutation of single nucleic acid was mainly influnced by codon usage. The value percentage of nonsynonymous substitutions (Ka) and synonymous substitutions (Ks) in 6Lagerstroemia species revealed that more photosynthesis genes have Ka or Ks only in Lagerstroemia fauriei, Lagerstroemia limii, and Lagerstroemia subcostata. These advances will facilitate the breeding of closely related Lagerstroemia species and deepen understanding on climatic adaptation of Lagerstroemia plants.